EFEKTIVITAS FUNGSI BAWASLU DALAM MENGAWASI TAHAPAN PEMILU 2019 DI KOTA PALEMBANG - Cali, Fatmalia; Amaliatulwalidain, Amaliatulwalidain; Nofrima, Sanny (JURNAL ILMIAH EDUNOMIKA, 2025)
This research was conducted with the aim of finding out the effectiveness of the function of the Palembang City Bawaslu in the 2019 Election stage process. In this research, the researcher usednqualitative methods, the data peroduced in this research is in the from of  written and spoken sentences so that it can describe issues regarding the effectivenes  the function in Palembang City Bawaslu the  supervising the  2019 election stages. The qualitative research approach used by researchers in the research is case studies, data collection techniques using three methods, namely obsevation, interviews and documentation. The results of the analysis and findings in the field from this research show that the  effectiveness of the function of the Palembang City Bawaslu in  supervising the  2019 election stages has severral obstacles in terms of facilities and infrastructure which have not been maximized, the effectiveness is function of the Palembang City Bawaslu in  supervising the  2019 election stages process, namely carrying out its duties and obeligations as well as its authority in the 2019 election, Bawaslu is not only a supervispry. Based on the results of the research and discussion carried out, the researchers came to a conclusion, namely the effectiveness function of the Palembang City Bawaslu in  supervising the  2019 election stages process, namely carrying out its duties and obeligations as well as its authority in the 2019 election through the process of plenning, supervising and implementing general election violations. As regulated in PKPU No. 5 Of 2018 concerning amandements to General Election Commiddion regulations no. 7 of 2017 concerningstages, programs and shedules for holding the 2019 general election.